Nonlinear updating method: a review - Bussetta, Philippe [UNESP]; Shiki, Sidney Bruce; da Silva, Samuel [UNESP] (Springer Nature, 2017)
This paper is a survey of the literature about the nonlinear updating process. It is focused on the computation of the difference between the numerical model and the reference data as well as the algorithm uses to find the optimal parameters. In both parts of the nonlinear updating process, the popular approaches are presented. Special emphasis is given to methods based on Volterra series.
Keywords: Model updating; Nonlinear identification; Nonlinear model; Sensitivity